The effects of porosity and angle of inclination on the deflection of fluid flow in porous media (2009)
"The movement of contaminated fluid from a solid waste landfill into a portable water aquifer located beneath is an example of unwanted underground flow with the problem of limited portion of land available for building construction in the cities, coupled with the rise in price of good and accessible land, there is a need for quick and urgent solutions to environmental pollution that may be resulted from this problem. In this research, a laboratory setup consisting of a big transparent cylindrical pipe 108 5cm long with radius 2 23cm was used as inlet pipe and five small equal transparent cylindrical pipes with radii 0.03cm were used as outlets, which were joined to the circular plastic plate on the top of the inlet pipe at different angles ranged from 0° to 90° from a normal point. The inlet pipe and outlets pipes were filled with samples of soil of different porosities and titled at different angles of inclination. The volume of water discharged was measured directly with measuring cylinder from the set-up in each case. The volumetric flow rate and volume flux were computed from the values of volume discharged. These were done in order to determine how the arrangement of porous material of different porosities with a particular angle of inclination can influence the deflection of fluid flow from its linear direction. This is sequel to its practical applications in designing a construction with a cross-section of soils in deflecting contaminated fluid from septic tank to different directions from the source of water within the same small portion of land. It was observed that angle of inclination does not have a significant effect on the deflection of fluid but volume flux increases with increasing angle of inclination. Also, the greater the difference in the porosity of the cross-section of the media in which the fluid is flowing the greater the volume flux However, the most suitable arrangement of cross-section of soils for deflection of fluid at higher angle from normal is when it flows through a medium of low porosity to that of higher porosity. "